2021
DOI: 10.1002/ajpa.24435
|View full text |Cite
|
Sign up to set email alerts
|

Hydatid disease (Echinococcosis granulosis) diagnosis from skeletal osteolytic lesions in an early seventh‐millennium BP forager community from preagricultural northern Vietnam

Abstract: Objectives: Con Co Ngua is a complex, sedentary forager site from northern Vietnam dating to the early seventh millennium BP. Prior research identified a calcified Echinococcus granulosis cyst, which causes hydatid disease. Osteolytic lesions consistent with hydatid disease were also present in this individual and others. Hydatid disease is observed in high frequencies in pastoralists, and its presence in a hunter-gatherer community raises questions regarding human-animal interaction prior to farming. The obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…As I have previously argued (Vlok, Buckley, et al, 2022), the use of terminology from the Istanbul protocol, is not entirely useful when adopting clinical literature as it is not used in clinical fields. Instead, the terms refer to examination of bodily signs of torture that are compared with a victim's story.…”
Section: Standardizing Terms In the Threshold Diagnostic Approachmentioning
confidence: 99%
“…As I have previously argued (Vlok, Buckley, et al, 2022), the use of terminology from the Istanbul protocol, is not entirely useful when adopting clinical literature as it is not used in clinical fields. Instead, the terms refer to examination of bodily signs of torture that are compared with a victim's story.…”
Section: Standardizing Terms In the Threshold Diagnostic Approachmentioning
confidence: 99%
“…There were very little differences in the prevalence of non‐specific stress markers such as linear enamel hypoplasia and cribra orbitalia at Man Bac and Con Co Ngua (Oxenham et al, 2018; Oxenham & Domett, 2011). We now know that the inhabitants of Con Co Ngua greatly suffered high infectious disease burdens including malaria, hydatid disease, as well as genetic anemia (Vlok et al, 2021, 2022), which would have obscured the differing nutritional trends contributing to non‐specific stress, and now revealed through investigation for evidence of scurvy in the assemblages. That is, while the morbidity of general physiological stress was similar, the contribution of nutritional and infectious diseases to these stressors differed greatly between Con Co Ngua and Man Bac.…”
Section: Discussionmentioning
confidence: 99%
“…New research has questioned a simplified definition of ‘decline’ in health and revealed a level of epidemiological complexity only visible through the diagnosis of specific infectious diseases. For example, Vlok et al (2020) and (2022) demonstrated a shift from environmentally driven to human driven infectious diseases with the adoption of agriculture in northern Vietnam. This region is a geographical friction zone between forager groups from MSEA and farmers from modern day southern China, eventually leading to both demographic and technological change (Bellwood & Oxenham, 2008; Higham, Guangmao, & Qiang, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Iron deficiency induced by parasites, including hookworm and roundworm, also contribute to high iron deficiency anemia morbidity in Southeast Asian children (Loukas et al, 2016). It should be noted that hydatid disease, caused by a parasitic tapeworm, was a significant burden at Con Co Ngua (Vlok et al, 2022); however, while anemia is commonly observed in infected individuals, it tends to be anemia of chronic disease/infection (Krige & Beckingham, 2001) which is not associated with the mechanisms that can lead to cribra orbitalia (Oxenham & Cavill, 2010).…”
Section: Discussionmentioning
confidence: 99%